Kako izboljšati kvaliteto življenja pri bolnikih s parkinsonizmom? - Rečnik, Gregor (Medicinski razgledi, 2003)
Parkinsonism is a chronic disorder of the central nervous system characterizedpathologically by degeneration of dopamine neurons in substantia nigra pars compacta. Consequently, striatal dopamine levels decrease resultingin classical motor signs (tremor, rigidity, akinesia, postural impairment). Recently, pathological changes have been described also in limbicand prefrontal cortices which may explain non-motor parkinsonian symptoms (dementia, depression). As yet there has been no study in Slovenia onhow various factors influence quality of life (QoL) in Parkinsonian patients. 71 patients were asked to assess quality of their life on a visual analogue scale and with EQ-5D instrument. According to the results on the VAS they were divided into two groups. The following parameters were studied in all patients: motor disability, impairment in daily activities, cognitive abilities, depression and self-assessment of their health state. Depression was assessed in carers. Our results show that depression and impairment in daily activities, but not motor or cognitive disability, influence, QoL in patients with parkinsonism. We propose that clinical examination of the patients includes not only motor assessment but also assessment of mood in patients and occasionally carers. Improvement in daily activities can be reached with a multidisciplinary team management of the patient.
Keywords: Dnevne aktivnosti; Parkinson Disease; Gibanje, motnje; Diagnosis; Kvaliteta življenja; Drug Therapy; Parkinsonova bolezen; Quality Of Life; Activities Of Daily Living; ankete; Bolečina; Movement Disorders; Neurologic Examination; Depresija; Nevrološka preiskava; Pain; Depression; bolniki; gibanje; Questionnaires; motnje